Microbial carbon use efficiency is governed by site-level soil and climate factors and does not explain soil carbon gains under diversified crop rotations - Timothy M. Bowles; Maria Mooshammer; A. Stuart Grandy; Kevin Geyer; Serita D. Frey; Francisco Calderón; Steve Culman; Bill Deen; Kari Dunfield; Virginia L. Jin; R. Michael Lehman; Shannon L. Osborne; et al. (Soil Biology and Biochemistry, 2026)

Shrub and sedge rhizosphere communities display distinct affinities toward exudates and soil organic matter degradation: a quantitative stable isotope probing analysis - Sean R. Schaefer; Steven J. Blazewicz; Hannah Holland-Moritz; Caitlin Hicks Pries; G. Mike Allen; Jennifer Pett-Ridge; Fernando Montaño-López; A. Stuart Grandy; William Wieder; Jessica G. Ernakovich (Soil Biology and Biochemistry, 2026)

Organo-mineral interactions in active layer and permafrost soils along aging Arctic landscapes - Fernando Montaño-López; Joshua D. Landis; Skylar D. Wilkins; Sean R. Schaefer; Ravi Kukkadapu; Sophie F. von Fromm; Stuart Grandy; Jessica Gilman Ernakovich; Caitlin Hicks Pries (CATENA, 2026)

Seasonal Flooding Disrupts Expected Depth‐Dependent Patterns of Mineral Associated Carbon, Nitrogen, and Phosphorus Across Land Uses - Hannah P. Lieberman; Christian von Sperber; Rachael Harman‐Denhoed; A. Stuart Grandy; Cynthia M. Kallenbach (Global Change Biology, 2026)
Approximately 25%–70% of soil organic matter (OM) is stored below 30 cm, rendering subsoil OM cycling an important control on OM persistence. With climate change, soils are experiencing new pedoclimatic disturbances like seasonal flooding that can destabilize mineral associated organic matter (MAOM) and undermine carbon (C), nitrogen (N), and phosphorus (P) persistence. Our current understanding of how OM cycles down the soil profile is largely based on well‐drained soils. Thus, it remains uncertain if expected depth‐dependent trends and subsoil OM persistence differ in soils subjected to seasonal flooding across land uses. We collected 1‐m‐deep soil cores within a seasonal floodplain, representing a land‐use gradient: forest, pasture, and cropland. We compared MAOM concentrations (C, N, and P), stoichiometry, isotopic, and molecular chemical composition, in combination with microbial biomass and carbon use efficiency at four soil depths to understand the transformation and persistence of OM with depth. We found that the composition of OM by depth in our soils diverges from common trends in well‐drained soils. For example, in well‐drained soils, we expect a decrease in mineral associated C:N, and an increase in polar compounds with depth, as these compounds are thought to be more persistent. Instead, we found an increase in MAOM C:N in the forest and cropland, and an increase in non‐polar C rich compounds in all land uses with depth. The pasture varied from the forest and cropland, with OM composition largely unchanged with depth. Our results suggest that the extensive root system in the pasture causes desorption of older compounds resulting in younger, plant derived compounds at all depths. We propose that the controls on persistence differ in a seasonal floodplain, where MAOM persistence is shaped more by compound resistance to hydrological stress than by formation pathways.

Soil Carbon Saturation: What Do We Really Know? - Katerina Georgiou; Denis Angers; Ryan E. Champiny; M. Francesca Cotrufo; Matthew E. Craig; Sebastian Doetterl; A. Stuart Grandy; Jocelyn M. Lavallee; Yang Lin; Emanuele Lugato; Christopher Poeplau; Katherine S. Rocci; et al. (Global Change Biology, 2025)
Managing soils to increase organic carbon storage presents a potential opportunity to mitigate and adapt to global change challenges, while providing numerous co‐benefits and ecosystem services. However, soils differ widely in their potential for carbon sequestration, and knowledge of biophysical limits to carbon accumulation may aid in informing priority regions. Consequently, there is great interest in assessing whether soils exhibit a maximum capacity for storing organic carbon, particularly within organo–mineral associations given the finite nature of reactive minerals in a soil. While the concept of soil carbon saturation has existed for over 25 years, recent studies have argued for and against its importance. Here, we summarize the conceptual understanding of soil carbon saturation at both micro‐ and macro‐scales, define key terminology, and address common concerns and misconceptions. We review methods used to quantify soil carbon saturation, highlighting the theory and potential caveats of each approach. Critically, we explore the utility of the principles of soil carbon saturation for informing carbon accumulation, vulnerability to loss, and representations in process‐based models. We highlight key knowledge gaps and propose next steps for furthering our mechanistic understanding of soil carbon saturation and its implications for soil management.

Aligning theoretical and empirical representations of soil carbon-to-nitrogen stoichiometry with process-based terrestrial biogeochemistry models - Katherine S. Rocci; Cory C. Cleveland; Brooke A. Eastman; Katerina Georgiou; A. Stuart Grandy; Melannie D. Hartman; Emma Hauser; Hannah Holland-Moritz; Emily Kyker-Snowman; Derek Pierson; Peter B. Reich; Else P. Schlerman; et al. (Soil Biology and Biochemistry, 2024)

Elevated atmospheric CO 2 drives decreases in stable soil organic carbon in arid ecosystems: Evidence from a physical fractionation and organic compound analysis - Kelsey H. Jensen; A. Stuart Grandy; Jed P. Sparks (Global Change Biology, 2024)
The increasing concentration of CO 2 in the atmosphere is perturbing the global carbon (C) cycle, altering stocks of organic C, including soil organic matter (SOM). The effect of this disturbance on soils in arid ecosystems may differ from other ecosystems due to water limitation. In this study, we conducted a density fractionation on soils previously harvested from the Nevada Desert FACE Facility (NDFF) to understand how elevated atmospheric CO 2 (eCO 2 ) affects SOM stability. Soils from beneath the perennial shrub, Larrea tridentata , and from unvegetated interspace were subjected to a sodium polytungstate density fractionation to separate light, particulate organic matter (POM, 3 ) from heavier, mineral associated organic matter (MAOM, >1.85 g/cm 3 ). These fractions were analyzed for organic C, total N, δ 13 C and δ 15 N, to understand the mechanisms behind changes. The heavy fraction was further analyzed by pyrolysis GC/MS to assess changes in organic compound composition. Elevated CO 2 decreased POM‐C and MAOM‐C in soils beneath L. tridentata while interspace soils exhibited only a small increase in MAOM‐N. Analysis of δ 13 C revealed incorporation of new C into both POM and MAOM pools indicating eCO 2 stimulated rapid turnover of both POM and MAOM. The largest losses of POM‐C and MAOM‐C observed under eCO 2 occurred in soils 20–40 cm in depth, highlighting that belowground C inputs may be a significant driver of SOM decomposition in this ecosystem. Pyrolysis GC/MS analysis revealed a decrease in organic compound diversity in the MAOM fraction of L. tridentata soils, becoming more similar to interspace soils under eCO 2 . These results provide further evidence that MAOM stability may be compromised under disturbance and that SOC stocks in arid ecosystems are vulnerable under continued climate change.

Molecular complexity and diversity of persistent soil organic matter - Andrew R. Jones; Ram C. Dalal; Vadakattu V.S.R. Gupta; Susanne Schmidt; Diane E. Allen; Geraldine E. Jacobsen; Michael Bird; A. Stuart Grandy; Jonathan Sanderman (Soil Biology and Biochemistry, 2023)

Complex crop rotations improve organic nitrogen cycling - Lauren C. Breza; Maria Mooshammer; Timothy M. Bowles; Virginia L. Jin; Marty R. Schmer; Bennett Thompson; A. Stuart Grandy (Soil Biology and Biochemistry, 2023)

Clarifying the evidence for microbial‐ and plant‐derived soil organic matter, and the path toward a more quantitative understanding - Emily D. Whalen; A. Stuart Grandy; Noah W. Sokol; Marco Keiluweit; Jessica Ernakovich; Richard G. Smith; Serita D. Frey (Global Change Biology, 2022)
Predicting and mitigating changes in soil carbon (C) stocks under global change requires a coherent understanding of the factors regulating soil organic matter (SOM) formation and persistence, including knowledge of the direct sources of SOM (plants vs. microbes). In recent years, conceptual models of SOM formation have emphasized the primacy of microbial‐derived organic matter inputs, proposing that microbial physiological traits (e.g., growth efficiency) are dominant controls on SOM quantity. However, recent quantitative studies have challenged this view, suggesting that plants make larger direct contributions to SOM than is currently recognized by this paradigm. In this review, we attempt to reconcile these perspectives by highlighting that variation across estimates of plant‐ versus microbial‐derived SOM may arise in part from methodological limitations. We show that all major methods used to estimate plant versus microbial contributions to SOM have substantial shortcomings, highlighting the uncertainty in our current quantitative estimates. We demonstrate that there is significant overlap in the chemical signatures of compounds produced by microbes, plant roots, and through the extracellular decomposition of plant litter, which introduces uncertainty into the use of common biomarkers for parsing plant‐ and microbial‐derived SOM, especially in the mineral‐associated organic matter (MAOM) fraction. Although the studies that we review have contributed to a deeper understanding of microbial contributions to SOM, limitations with current methods constrain quantitative estimates. In light of recent advances, we suggest that now is a critical time to re‐evaluate long‐standing methods, clearly define their limitations, and develop a strategic plan for improving the quantification of plant‐ and microbial‐derived SOM. From our synthesis, we outline key questions and challenges for future research on the mechanisms of SOM formation and stabilization from plant and microbial pathways.

Increasing the spatial and temporal impact of ecological research: A roadmap for integrating a novel terrestrial process into an Earth system model - Emily Kyker‐Snowman; Danica L. Lombardozzi; Gordon B. Bonan; Susan J. Cheng; Jeffrey S. Dukes; Serita D. Frey; Elin M. Jacobs; Risa McNellis; Joshua M. Rady; Nicholas G. Smith; R. Quinn Thomas; William R. Wieder; et al. (Global Change Biology, 2022)
Terrestrial ecosystems regulate Earth's climate through water, energy, and biogeochemical transformations. Despite a key role in regulating the Earth system, terrestrial ecology has historically been underrepresented in the Earth system models (ESMs) that are used to understand and project global environmental change. Ecology and Earth system modeling must be integrated for scientists to fully comprehend the role of ecological systems in driving and responding to global change. Ecological insights can improve ESM realism and reduce process uncertainty, while ESMs offer ecologists an opportunity to broadly test ecological theory and increase the impact of their work by scaling concepts through time and space. Despite this mutualism, meaningfully integrating the two remains a persistent challenge, in part because of logistical obstacles in translating processes into mathematical formulas and identifying ways to integrate new theories and code into large, complex model structures. To help overcome this interdisciplinary challenge, we present a framework consisting of a series of interconnected stages for integrating a new ecological process or insight into an ESM. First, we highlight the multiple ways that ecological observations and modeling iteratively strengthen one another, dispelling the illusion that the ecologist's role ends with initial provision of data. Second, we show that many valuable insights, products, and theoretical developments are produced through sustained interdisciplinary collaborations between empiricists and modelers, regardless of eventual inclusion of a process in an ESM. Finally, we provide concrete actions and resources to facilitate learning and collaboration at every stage of data‐model integration. This framework will create synergies that will transform our understanding of ecology within the Earth system, ultimately improving our understanding of global environmental change, and broadening the impact of ecological research.

Anthropogenic N deposition alters soil organic matter biochemistry and microbial communities on decaying fine roots - William A. Argiroff; Donald R. Zak; Rima A. Upchurch; Sydney O. Salley; A. Stuart Grandy (Global Change Biology, 2019)
Fine root litter is a primary source of soil organic matter (SOM), which is a globally important pool of C that is responsive to climate change. We previously established that ~20 years of experimental nitrogen (N) deposition has slowed fine root decay and increased the storage of soil carbon (C; +18%) across a widespread northern hardwood forest ecosystem. However, the microbial mechanisms that have directly slowed fine root decay are unknown. Here, we show that experimental N deposition has decreased the relative abundance of Agaricales fungi (−31%) and increased that of partially ligninolytic Actinobacteria (+24%) on decaying fine roots. Moreover, experimental N deposition has increased the relative abundance of lignin‐derived compounds residing in SOM (+53%), and this biochemical response is significantly related to shifts in both fungal and bacterial community composition. Specifically, the accumulation of lignin‐derived compounds in SOM is negatively related to the relative abundance of ligninolytic Mycena and Kuehneromyces fungi, and positively related to Microbacteriaceae. Our findings suggest that by altering the composition of microbial communities on decaying fine roots such that their capacity for lignin degradation is reduced, experimental N deposition has slowed fine root litter decay, and increased the contribution of lignin‐derived compounds from fine roots to SOM. The microbial responses we observed may explain widespread findings that anthropogenic N deposition increases soil C storage in terrestrial ecosystems. More broadly, our findings directly link composition to function in soil microbial communities, and implicate compositional shifts in mediating biogeochemical processes of global significance.

Soil carbon cycling proxies: Understanding their critical role in predicting climate change feedbacks - Vanessa L. Bailey; Ben Bond‐Lamberty; Kristen DeAngelis; A. Stuart Grandy; Christine V. Hawkes; Kate Heckman; Kate Lajtha; Richard P. Phillips; Benjamin N. Sulman; Katherine E. O. Todd‐Brown; Matthew D. Wallenstein (Global Change Biology, 2018)
The complexity of processes and interactions that drive soil C dynamics necessitate the use of proxy variables to represent soil characteristics that cannot be directly measured (correlative proxies), or that aggregate information about multiple soil characteristics into one variable (integrative proxies). These proxies have proven useful for understanding the soil C cycle, which is highly variable in both space and time, and are now being used to make predictions of the fate and persistence of C under future climate scenarios. However, the C pools and processes that proxies represent must be thoughtfully considered in order to minimize uncertainties in empirical understanding. This is necessary to capture the full value of a proxy in model parameters and in model outcomes. Here, we provide specific examples of proxy variables that could improve decision‐making, and modeling skill, while also encouraging continued work on their mechanistic underpinnings. We explore the use of three common soil proxies used to study soil C cycling: metabolic quotient, clay content, and physical fractionation. We also consider how emerging data types, such as genome‐sequence data, can serve as proxies for microbial community activities. By examining some broad assumptions in soil C cycling with the proxies already in use, we can develop new hypotheses and specify criteria for new and needed proxies.

Comparison of measured multi-decadal rainfall variability with farmers’ perceptions of and responses to seasonal changes in western Uganda - Jeremy E. Diem; Joel Hartter; Jonathan Salerno; Elvira McIntyre; A. Stuart Grandy (Regional Environmental Change, 2017)

Applying population and community ecology theory to advance understanding of belowground biogeochemistry - Robert W. Buchkowski; Mark A. Bradford; Andrew Stuart Grandy; Oswald J. Schmitz; William R. Wieder (Ecology Letters, 2017)
Approaches to quantifying and predicting soil biogeochemical cycles mostly consider microbial biomass and community composition as products of the abiotic environment. Current numerical approaches then primarily emphasise the importance of microbe–environment interactions and physiology as controls on biogeochemical cycles. Decidedly less attention has been paid to understanding control exerted by community dynamics and biotic interactions. Yet a rich literature of theoretical and empirical contributions highlights the importance of considering how variation in microbial population ecology, especially biotic interactions, is related to variation in key biogeochemical processes like soil carbon formation. We demonstrate how a population and community ecology perspective can be used to (1) understand the impact of microbial communities on biogeochemical cycles and (2) reframe current theory and models to include more detailed microbial ecology. Through a series of simulations we illustrate how density dependence and key biotic interactions, such as competition and predation, can determine the degree to which microbes regulate soil biogeochemical cycles. The ecological perspective and model simulations we present lay the foundation for developing empirical research and complementary models that explore the diversity of ecological mechanisms that operate in microbial communities to regulate biogeochemical processes.

The origin of litter chemical complexity during decomposition - Kyle Wickings; A. Stuart Grandy; Sasha C. Reed; Cory C. Cleveland (Ecology Letters, 2012)
The chemical complexity of decomposing plant litter is a central feature shaping the terrestrial carbon ( C ) cycle, but explanations of the origin of this complexity remain contentious. Here, we ask: How does litter chemistry change during decomposition, and what roles do decomposers play in these changes? During a long‐term (730 days) litter decomposition experiment, we tracked concurrent changes in decomposer community structure and function and litter chemistry using high‐resolution molecular techniques. Contrary to the current paradigm, we found that the chemistry of different litter types diverged, rather than converged, during decomposition due to the activities of decomposers. Furthermore, the same litter type exposed to different decomposer communities exhibited striking differences in chemistry, even after > 90% mass loss. Our results show that during decomposition, decomposer community characteristics regulate changes in litter chemistry, which could influence the functionality of litter‐derived soil organic matter ( SOM ) and the turnover and stabilisation of soil C.

Experimental litterfall manipulation drives large and rapid changes in soil carbon cycling in a wet tropical forest - Jonathan W. Leff; William R. Wieder; Philip G. Taylor; Alan R. Townsend; Diana R. Nemergut; A. Stuart Grandy; Cory C. Cleveland (Global Change Biology, 2012)
Global changes such as variations in plant net primary production are likely to drive shifts in leaf litterfall inputs to forest soils, but the effects of such changes on soil carbon ( C ) cycling and storage remain largely unknown, especially in C ‐rich tropical forest ecosystems. We initiated a leaf litterfall manipulation experiment in a tropical rain forest in C osta R ica to test the sensitivity of surface soil C pools and fluxes to different litter inputs. After only 2 years of treatment, doubling litterfall inputs increased surface soil C concentrations by 31%, removing litter from the forest floor drove a 26% reduction over the same time period, and these changes in soil C concentrations were associated with variations in dissolved organic matter fluxes, fine root biomass, microbial biomass, soil moisture, and nutrient fluxes. However, the litter manipulations had only small effects on soil organic C ( SOC ) chemistry, suggesting that changes in C cycling, nutrient cycling, and microbial processes in response to litter manipulation reflect shifts in the quantity rather than quality of SOC . The manipulation also affected soil CO 2 fluxes; the relative decline in CO 2 production was greater in the litter removal plots (−22%) than the increase in the litter addition plots (+15%). Our analysis showed that variations in CO 2 fluxes were strongly correlated with microbial biomass pools, soil C and nitrogen ( N ) pools, soil inorganic P fluxes, dissolved organic C fluxes, and fine root biomass. Together, our data suggest that shifts in leaf litter inputs in response to localized human disturbances and global environmental change could have rapid and important consequences for belowground C storage and fluxes in tropical rain forests, and highlight differences between tropical and temperate ecosystems, where belowground C cycling responses to changes in litterfall are generally slower and more subtle.

Roots and fungi accelerate carbon and nitrogen cycling in forests exposed to elevated CO 2 - Richard P. Phillips; Ina C. Meier; Emily S. Bernhardt; A. Stuart Grandy; Kyle Wickings; Adrien C. Finzi (Ecology Letters, 2012)
A common finding in multiple CO 2 enrichment experiments in forests is the lack of soil carbon ( C ) accumulation owing to microbial priming of ‘old’ soil organic matter ( SOM ). However, soil C losses may also result from the accelerated turnover of ‘young’ microbial tissues that are rich in nitrogen ( N ) relative to bulk SOM . We measured root‐induced changes in soil C dynamics in a pine forest exposed to elevated CO 2 and N enrichment by combining stable isotope analyses, molecular characterisations of SOM and microbial assays. We find strong evidence that the accelerated turnover of root‐derived C under elevated CO 2 is sufficient in magnitude to offset increased belowground inputs. In addition, the C losses were associated with accelerated N cycling, suggesting that trees exposed to elevated CO 2 not only enhance N availability by stimulating microbial decomposition of SOM via priming but also increase the rate at which N cycles through microbial pools.

The Effects of Soil Bacterial Community Structure on Decomposition in a Tropical Rain Forest - Jonathan W. Leff; Diana R. Nemergut; A. Stuart Grandy; Sean P. O’Neill; Kyle Wickings; Alan R. Townsend; Cory C. Cleveland (Ecosystems, 2012)

Land-Use Intensity Effects on Soil Organic Carbon Accumulation Rates and Mechanisms - A. Stuart Grandy; G. Philip Robertson (Ecosystems, 2007)

Initial cultivation of a temperate‐region soil immediately accelerates aggregate turnover and CO 2 and N 2 O fluxes - A. STUART GRANDY; G. PHILIP ROBERTSON (Global Change Biology, 2006)
The immediate effects of tillage on protected soil C and N pools and on trace gas emissions from soils at precultivation levels of native C remain largely unknown. We measured the response to cultivation of CO 2 and N 2 O emissions and associated environmental factors in a previously uncultivated U.S. Midwest Alfisol with C concentrations that were indistinguishable from those in adjacent late successional forests on the same soil type (3.2%). Within 2 days of initial cultivation in 2002, tillage significantly ( P =0.001, n =4) increased CO 2 fluxes from 91 to 196 mg CO 2 ‐C m −2 h −1 and within the first 30 days higher fluxes because of cultivation were responsible for losses of 85 g CO 2 ‐C m −2 . Additional daily C losses were sustained during a second and third year of cultivation of the same plots at rates of 1.9 and 1.0 g C m −2 day −1 , respectively. Associated with the CO 2 responses were increased soil temperature, substantially reduced soil aggregate size (mean weight diameter decreased 35% within 60 days), and a reduction in the proportion of intraaggregate, physically protected light fraction organic matter. Nitrous oxide fluxes in cultivated plots increased 7.7‐fold in 2002, 3.1‐fold in 2003, and 6.7‐fold in 2004 and were associated with increased soil NO 3 − concentrations, which approached 15 μg N g −1 . Decreased plant N uptake immediately after tillage, plus increased mineralization rates and fivefold greater nitrifier enzyme activity, likely contributed to increased NO 3 − concentrations. Our results demonstrate that initial cultivation of a soil at precultivation levels of native soil C immediately destabilizes physical and microbial processes related to C and N retention in soils and accelerates trace gas fluxes. Policies designed to promote long‐term C sequestration may thus need to protect soils from even occasional cultivation in order to preserve sequestered C.